Factors associated with the COVID-19 vaccine choice of undergraduate students of state universities in Tacloban City - Avelino, Hannah Mae B.; Cadilo, Daniela A.; Gannaban, Greggory Marc D. (2022)
This study determined the COVID-19 vaccine choice of students of state universities in Tacloban City and the factors significantly associated with the same. An online survey was conducted among 196 undergraduate participants from UPVTC and EVSU obtained through self-selection and snowball sampling. The raw data generated was then analyzed using STATA. Descriptive statistics were applied to the respondents' demographic information, willingness to be vaccinated, answers to the Likert scale questions, and COVID-19 vaccine choice. Cramer's V test was employed to analyze the strength of association between the demographic factors, willingness to be vaccinated, vaccine characteristics, attitude towards vaccination, social factors, and the COVID-19 vaccine choice of the respondents. The significance of the association of each factor to the COVID-19 vaccine choice of the respondents were analyzed using multinomial logistic regression. The results of the statistical tests show that: (1) the majority of respondents choose Pfizer BioNTech vaccine; (2) willingness to be vaccinated has a strong association with the COVID-19 vaccine choice of the participants while the majority of factors have a strong association with COVID-19 vaccine choice; (3) respondents' COVID-19 vaccine choice for Oxford AstraZeneca over Pfizer is significantly associated with vaccine availability; (4) three factors namely vaccine availability, perceived severity of diseases, and media are significantly associated with the respondents' choice for Sinovac CoronaVac over Pfizer; and (5) the respondents' choice for J&J Janssen, Moderna, and Sinopharm over Pfizer is not siginificantly associated with any of the factors.